A proposed framework for practical multimodal management of osteoarthritis in growing dogs - Marcellin-Little, Denis J.; Hulse, Donald A.; Huntingford, Janice L.; Grubb, Tamara; Brunke, Matthew W.; Markley, Arielle Pechette; Frank, Bethany (Frontiers in Veterinary Science, 2025)
Osteoarthritis (OA) is a ubiquitous problem affecting dog joints, particularly the hip, elbow, stifle, and spine. OA most often results from developmental orthopedic problems such as hip dysplasia, elbow dysplasia, and patellar luxation and from injuries to the cranial cruciate ligament. Several management approaches have been proposed to manage OA, including steps to modulate growth, physical activity, and exercise, nutrition and nutritional supplementation, medications, physical rehabilitation, and surgical procedures. This article is the first in a series of articles that propose steps for practical OA management in dogs at various life stages. The review presented here focuses on growing dogs. The text describes the early pathophysiology and diagnosis of OA. The physical, nutritional, analgesic, and surgical management options of OA in growing dogs are presented. The application of these management options is described for three dogs. The overall approach to the management of OA in growing dogs is discussed.